Bi-Metal Deposits within Nanostructured Silicon with Respect to Permanent Nanomagnets. (19th June 2018) - Rumpf, Klemens; Granitzer, Petra; Michor, Herwig; Poelt, Peter
Abstract : The purpose of this work is to fabricate nanostructured silicon with two different materials of embedded magnetic nanostructures to exploit the magnetic properties of both metals and gain control of the exchange coupling between the two metals especially with respect to their volume ratio. Generally both metals are deposited alternatingly out of one solution by varying the applied potential but in a further approach the two metals are also deposited by using different metal salt solutions alternately. Furthermore a variation of the structure size and the proximity of the metal deposits modifies the exchange coupling and thus the energy product. Finally nanocomposits with an energy product as high as possible are achieved to give rise to on-chip applications using permanent nanomagnets, especially arranged in arrays.